2019
DOI: 10.3389/fpsyt.2019.00762
|View full text |Cite|
|
Sign up to set email alerts
|

Violent Behavior During Psychiatric Inpatient Treatment in a German Prison Hospital

Abstract: Violent behavior in correctional facilities is common and differs substantially in type, target, implication, and trigger. Research on frequency and characteristics of violent behavior in correctional facilities and psychiatric hospitals is limited. Results from recent research suggest that comorbidity of severe mental disorder, personality disorder, and diagnosis of substance abuse is related to a higher risk of violent behavior. In the Berlin prison hospital, a database was created to collect data from all v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…Psychotic symptoms such as paranoid delusions have also been associated with violence in the past (Coid et al, 2013;Maier, Hauth, Berger, & Saß, 2016). An association between schizophrenia and the frequency of violence was also found in a German study, but the authors stated that violence was in total not more frequent than that reported from a psychiatric community hospital (Seidel et al, 2019). A systematic review and meta-analysis from 2009 including 20 studies and a total of 18,423 patients with schizophrenia and psychotic disorders confirmed that the additional diagnosis of substance abuse disorder is a risk factor for violent behavior (Fazel, Gulati, Linsell, Geddes, & Grann, 2009).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Psychotic symptoms such as paranoid delusions have also been associated with violence in the past (Coid et al, 2013;Maier, Hauth, Berger, & Saß, 2016). An association between schizophrenia and the frequency of violence was also found in a German study, but the authors stated that violence was in total not more frequent than that reported from a psychiatric community hospital (Seidel et al, 2019). A systematic review and meta-analysis from 2009 including 20 studies and a total of 18,423 patients with schizophrenia and psychotic disorders confirmed that the additional diagnosis of substance abuse disorder is a risk factor for violent behavior (Fazel, Gulati, Linsell, Geddes, & Grann, 2009).…”
mentioning
confidence: 79%
“…Finally, there is evidence for a relationship between suffering from schizophrenia and the frequency of violent incidents, which, however, were not assumed to have been overall more frequent than in patients in community mental health care (Seidel et al, 2019). This would also correspond to a similar level of expression of the positive psychotic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Da die Maßregelvollzugskliniken auf die Behandlung psychiatrischer Erkrankungen ausgerichtet sind, erscheint nachvollziehbar, dass psychiatrische Störungsbilder in diesen Einrichtungen zuverlässiger erfasst wurden als in den Justizvollzugsanstalten. Außerdem sind Interventionen in den Justizvollzugsanstalten stärker auf den Umgang mit aggressiven Personen ausgerichtet und Personen, die sich aufgrund einer psychiatrischen Störung ruhig und zurückgezogen verhalten, wird in der Regel weniger Aufmerksamkeit zuteil [ 36 ]. Insbesondere Rückzug und gedrückte Stimmung fallen in Justizvollzugsanstalten mit langen Einschlusszeiten und daraus folgendem eingeschränkten Kontaktangebot wenig auf oder werden als angemessene Reaktion fehlverstanden, obwohl eigentlich eine depressive Entwicklung vorliegt.…”
Section: Ursachen Und Risikofaktorenunclassified
“…While a prison hospital setting is comparable to high‐security forensic units, the patient needs reflect rather general psychiatric care. Thus, typical clinical indications for admission are (exacerbation of) psychosis, suicidal ideation, violent behavior of unclear origin, depression, and adjustment disorders with comorbid personality disorders and substance abuse disorders (Seidel et al, 2019). If the criminal responsibility of a remand prisoner is found to be diminished during the trial, he can be transferred to a forensic psychiatric hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the prevalence of violent behavior in medical and mental health settings are limited, especially for prison and forensic psychiatric environments. In a recent study, Seidel et al demonstrated that the prevalence of patients exhibiting violent behavior in the Berlin Prison Hospital in Germany ranged from 3.2 to 15.9% during the years from 2010 to 2016 without a significant increase over this period (Seidel et al, 2019). In general psychiatry, a moderate rise in violent behavior was reported recently in Germany, while this was not the case for the USA (Müller, Olschinski, Jochim, & Feldhordt, 2017; Staggs, 2015).…”
Section: Introductionmentioning
confidence: 99%